Optimization of Empowerment Strategies for Shrimp Cracker SMEs to Enhance Income and Competitiveness - Zaky Jahisam, Ahmad; Musthofa , M. Arif; Sunarti, Zeni; Kartika Devi, Erwina; Fatimah, Siti (Journal of Economics and Social Sciences (JESS), 2025)
This study examines the empowerment strategies implemented by the Cempaka 2 Wood-Fired Shrimp Crackers MSME in Kelurahan Mendahara Ilir, which significantly enhance income and product competitiveness in both local and external markets. Employing a qualitative descriptive approach, the research identifies key strategies such as continuous product quality improvement through training and innovation in flavor variants and hygienic packaging, the development of integrated marketing networks combining traditional and digital platforms, managerial training for human resource capacity building, and sustainable utilization of abundant local raw materials. The study contributes novel insights into integrating product innovation tailored to modern consumer preferences and the successful transition of traditional MSMEs into digital marketing channels. Additionally, it highlights the socio-cultural role of MSMEs in preserving local identity and cultural heritage, alongside environmental sustainability through coastal ecosystem preservation. The findings provide valuable recommendations for policymakers, business actors, and stakeholders to foster sustainable MSME development that balances economic, social, and cultural dimensions, ultimately supporting inclusive local economic growth